2022
DOI: 10.3390/en15030834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Substrate to Inoculum Ratios on the Kinetics of Biogas Production during the Mesophilic Anaerobic Digestion of Food Waste

Abstract: This study evaluates the effects of the varying substrate to inoculum ratios (S:I) of 0.5, 1, 2, 3, 4, 5, and 6 (volatile solids/VS basis) on the kinetics of biogas production during batch mesophilic (35 ± 1 ℃) anaerobic digestion (AD) of simulated food waste (FW), using anaerobic digestate as the inoculum. Kinetic parameters during biogas production (scrubbed with NaOH solution) are predicted by the first-order and the modified Gompertz model. The observed average specific biogas yields are in descending orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 44 publications
0
22
0
3
Order By: Relevance
“…Furthermore, the model demonstrated that the CMFW substrates had a higher biogas potential than a recent study ( Khadka et al, 2022 ). The authors obtained the value of R m as 0.0252 L/day.…”
Section: Resultsmentioning
confidence: 61%
“…Furthermore, the model demonstrated that the CMFW substrates had a higher biogas potential than a recent study ( Khadka et al, 2022 ). The authors obtained the value of R m as 0.0252 L/day.…”
Section: Resultsmentioning
confidence: 61%
“…The cumulative biogas yield obtained from this study was fitted to the modified Gompertz model described by Equation [42] M=normalBnormalp×exp-normalenormalxnormalp[]normalBnormalm.eBpλ-normalt+1=normalBnormalp×1-normalenormalxnormalp()-kt $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm M}={{\rm B}}_{{\rm p}}\times {\rm e}{\rm x}{\rm p}\left\{-{\rm e}{\rm x}{\rm p}\left[{{{{\rm B}}_{{\rm m}}.…”
Section: Resultsmentioning
confidence: 99%
“…The effective methane production time, T eff , calculated by subtracting the lag phase from the time required to obtain 90% of the cumulative BMP, was 17 days for all silages. Neither an increase in TS nor the presence of additive had an effect on T eff , probably because all experiments were conducted at the same initial pH and inoculum‐to‐substrate ratio 51 . Mao et al 52 .…”
Section: Resultsmentioning
confidence: 99%
“…Neither an increase in TS nor the presence of additive had an effect on T eff , probably because all experiments were conducted at the same initial pH and inoculum-to-substrate ratio. 51 Mao et al 52 reported that longer T eff (19.2 days) was obtained at higher initial pH (7.5) compared to lower initial pH (6.0 and 6.5) during the co-digestion of swine manure and corn straw. In the present study, T eff obtained from the dual-pool model was the same as T eff obtained from the measured data, another indication that the model was most appropriate in predicting the BMP of the silages compared to the other two models.…”
Section: Kinetic Models and Validationmentioning
confidence: 99%